An Evaluation and Proposal of Growth Hormones in Beef - Stretcher, Kayla N. (URJ-UCCS: Undergraduate Research Journal at UCCS, 2011)
Beef growth hormones are a controversial subject on many sides. These sides include stakeholders of all areas such as environmentalists, the government, and consumers. While the dangerous effects of growth hormones on the human body are less commonly known to the public, those who take an anti-growth hormone view take a strong stance on working to limit the use of hormones and their potential effects. These effects prove to be harmful to the human body, causing the current hormone use in beef to be worthy of reform.